Self-assembled transdermal nanogels control scar formation by inhibiting fibroblast proliferation and fibrosis with glycolysis regulation via the PI3K/Akt/mTOR pathway - Xinxian Meng; Zhixi Yu; Shiqi Wu; Wanyu Xu; Yuzhen Tang; Zixuan Chen; Yixin Zhang; Yunsheng Chen; Zheng Zhang (Journal of Nanobiotechnology)
Abstract Hypertrophic scar (HS) is one of the most common challenges in the field of plastic and reconstructive surgery. HS formation is associated with the abnormal activation of fibroblasts. These fibroblasts exhibit excessive proliferative and fibrotic behavior, which can be induced by glycolysis dysregulation. Herein, self-assembled nanogels prepared by modifying IR808 with hyaluronic acid (termed HA-IR808) are introduced as selective glycolytic inhibitors to control HS formation through transdermal delivery to HS fibroblasts (HFs). HA-IR808 preferentially targets activated HFs and has a structure suitable for transdermal delivery. In vitro, HA-IR808 exhibits a glycolysis inhibition effect and regulates the fibrotic behavior and proliferation of HFs through energy depletion and macromolecule synthesis. In vivo, HA-IR808 penetrates the dermal layer, regulates glycolysis, and controls HS formation. Mechanistically, HA-IR808 regulates glycolysis by silencing the phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of the rapamycin (mTOR) signaling pathway. In conclusion, this research elucidates a strategy for controlling HS formation via glycolysis regulation using self-assembled HA-IR808 nanogels to inhibit HF activation. Graphical abstract